Project-Based E-Learning and Its Impact on Students’ Academic Achievement in Curriculum Development Lectures - Anak Agung Gede Agung; Basilius Redan Werang; Anak Agung Putri Sri (Mimbar Ilmu, 2022)
In recent years, using technology is very important in learning activities, so everyone must be able to use technology wisely. This study describes the potential impact of project-based e-learning on the academic achievement of fourth-semester students in curriculum development courses. This type of research is quantitative, using an experimental research design. The methods used to collect data are observation and tests. The instruments used in collecting data are observation sheets and test questions. The research subjects were 30 students. The data obtained were initially planned to be analyzed using the correlational sample t-test analysis technique. However, because the research data were not normally distributed, the research data were finally analyzed using non-parametric statistical analysis. The results of the data analysis show that first, there are no students whose posttest scores are lower than the pretest scores. Second, there were 23 students whose scores increased from the pretest to the posttest. Third, 6 students experienced identical scores from the pretest to the posttest. It was concluded that there were significant differences in student academic achievement in curriculum development courses before and after implementing project-based e-learning.